An Audit on the Role of Sentinel Lymph Node Biopsy (SLNB) in High Risk of Invasion DCIS and Encysted Papillary Carcinoma (Global Journal of Medical Research, 2023)
Background The incidence of breast ductal Carcinoma in Situ DCIS has been increasing it currently represents up to 20-25 of all breast carcinomas Encysted papillary cancer EPC is a rare form of breast carcinoma previously compared to DCIS which has been shown to present histologically with invasion of the basement membrane and even metastasis Aims Our objective was to define a high risk group of patients with pre-op diagnosis of noninvasive cancer undergoing breast conserving surgery BCS who would then benefit from SLNB Methods A retrospective data collection including all the patients with DCIS over the last 5 years was performed High risk was defined as Extensive micro-calcification 40mm or any mass forming DCIS EPC patients were collected via a Winpath search
Keywords: ductal carcinoma in situ; sentinel lymph node biopsy; encysted papillary carcinoma